Validation of the Unfaulted Error Bounds for ARAIM. Issue 1 (19th February 2018) - Walter, Todd; Gunning, Kazuma; Eric Phelts, R.; Blanch, Juan
Abstract: This paper examines how to evaluate observed instantaneous signal‐in‐space errors and determine suitable upper bounds on their likely distribution. We compare this performance against the commitments and broadcast values from the satellites to determine whether the provided values are sufficient or not. An important aspect is to characterize the errors in light of known or predictable characteristics. Oftentimes, errors are grouped together to create a single averaged distribution. However, there may be times and conditions where performance is notably worse. We need to separate out such conditions and evaluate the distributions individually so as not to form overly optimistic estimates of the error bounds. Further, we must ensure that these parameters will continue to bound future fault‐free behavior. We will describe the conservative steps taken in the estimation process and the validation effort, both with the real data and versus the stated commitments from the constellation service providers. Copyright © 2018 Institute of Navigation